Situacoes causadoras de "stress" no basquetebol de alto rendimento: Fatores competitivos - de Rose Junior, D.; Deschamps, S.; Korsakas, P. (Revista Paulista Educação Física, 1999)
One of the most important psychological aspects for athletes is stress. It is very important to know which are the situations that can lead athletes to stress in order to minimize the consequences in their performance. This research had two purposes: to identify stressing situations related to the competitive process and to categorize those situations in sources and factors of stress. The study was made with 19 basketball players (10 men and nine women) with age ranging from 23 to 38 years. All the athletes have been participating in international competitions representing Brazilian National Team. The data were collected through semi-structured interviews. Those interviews were analyzed by the authors. 114 competitive stressing situations were found and categorized into 24 sources of stress, representing the following specific factors: psychological states, physical aspects, game, team preparation, important people, planning/organization and social evaluation. Psychological states and physical aspects were defined as individual competitive factors (20 stressing situations). 16 of these situations were related to psychological states (fears, doubts and self pressures). The others were called situational competitive factors (94 stressing situations). 44 of these stressing situations were related to the game (importance and difficulty of the game, coach, teammates, opponents, referees and self competence). Other important sources of stress were important people (26 situations) and planning/organization (14 situations). Full text: http://www.usp.br/eef/rpef/v13n2/v13n2p217.pdf